Carbohydrate Supplementation Influences Serum Cytokines after Exercise under Hypoxic Conditions - Caris, Aline Venticinque; Da Silva, Edgar Tavares; Dos Santos, Samile Amorim; Lira, Fabio Santos [UNESP]; Oyama, Lila Missae; Tufik, Sergio; Thomatieli Dos Santos, Ronaldo Vagner (Mdpi Ag, 2016)
Introduction: Exercise performed at the hypoxia equivalent of an altitude of 4200 m is associated with elevated inflammatory mediators and changes in the Th1/Th2 response. By contrast, supplementation with carbohydrates has an anti-inflammatory effect when exercise is performed under normoxic conditions. The objective of this study was to evaluate the effect of carbohydrate supplementation on cytokines and cellular damage markers after exercise under hypoxic conditions at a simulated altitude of 4200 m. Methods: Seven adult male volunteers who exercised for 60 min at an intensity of 50% VO2Peak were randomly evaluated under three distinct conditions; normoxia, hypoxia and hypoxia + carbohydrate supplementation. Blood samples were collected at rest, at the end of exercise and after 60 min of recovery. To evaluate hypoxia + carbohydrate supplementation, volunteers received a solution of 6% carbohydrate (maltodextrin) or a placebo (strawberry-flavored Crystal Light (R); Kraft Foods, Northfield, IL, USA) every 20 min during exercise and recovery. Statistical analyses comprised analysis of variance, with a one-way ANOVA followed by the Tukey post hoc test with a significance level of p < 0.05. Results: Under normoxic and hypoxic conditions, there was a significant increase in the concentration of IL-6 after exercise and after recovery compared to at rest (p < 0.05), while in the hypoxia + carbohydrate group, there was a significant increase in the concentration of IL-6 and TNF-alpha after exercise compared to at rest (p < 0.05). Furthermore, under this condition, TNF-alpha, IL-2 and the balance of IL-2/IL-4 were increased after recovery compared to at rest (p < 0.05). Conclusion: We conclude that carbohydrate supplementation modified the IL-6 and TNF-alpha serum concentrations and shifted the IL-2/IL-4 balance towards Th1 in response without glycemic, glutaminemia and cell damage effects.
Keywords: supplementation; carbohydrate; hypoxia; exercise; immune system; IL-2/IL-4